Maritime metaphorics in modernist literature - Slabbert, T (2021)
This thesis explores the metaphoric role that the maritime world plays in modernist literature. Specifically, I make the case for a historically grounded modernist maritime metaphorics, by which authors draw on the material history of a pervasive maritime world in the late 19th and early 20th centuries in their engagements with signature topics such as the city (Joseph Conrad), perception (Virginia Woolf and H.D.), expatriation (T.S. Eliot), and right-wing politics (Ezra Pound). Combining perspectives from the New Modernist Studies and Oceanic Studies, my thesis focuses on a historicist turn in the critique of modernist literature's use of marine metaphors, tracing the ways in which naval competition, a global maritime economy, scientific innovation in marine biology, and maritime imperialism are reflected and interrogated in figurative language in the period. Reading the work of canonical authors such as Conrad, Woolf, H.D., Eliot, and Pound, I catalogue the ways in which differing and conflicting deployments of the sea, of the submarine, and of drowning are used, in their work, to reflect, interrogate, or advocate for a specifically maritime world order. This maritime world, I argue, constitutes an important and neglected context for the emergence and the development of Anglo-American modernism. This thesis thus offers a corrective to the occlusion of the maritime as a context for modernism, and provides an example of a historicist reading of maritime metaphors that have largely been dismissed as clichés or ahistorical flights of fancy.